THE RELATIONSHIP BETWEEN PSYCHOLOGICAL COPING SKILLS AND FEAR OF FAILURE IN SENIOR MALE FUTSAL ATHLETES - Muhammad Hu Gardani; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian; Selmia Pasang (Jurnal Saintifik (Multi Science Journal), 2026)
Futsal athletes often experience difficulties in dealing with pressure, so that athletes cannot show their best performance, such as pressure from the audience, from coaches and various other things. However, in this case, excessive pressure can cause anxiety or fear in athletes, this shows that the psychological readiness of athletes is an important factor to support athlete performance in competitions, especially in futsal sports that require coping skills to face pressure and the possibility of failure. This study aims to examine the relationship between Psychological coping skills and Fear of failure in senior futsal athletes. This study uses a descriptive method with a quantitative approach and then uses the ACSI-28 and PFAI instruments which are given once to the sample after the data is collected. Data analysis is carried out using a correlation test through the SPSS software application. The results show a correlation coefficient value of 0.611 with a significance value of 0.0001 (p <0.05), which indicates that there is a significant negative relationship between psychological coping skills and fear of failure in senior male futsal athletes with a strong relationship category. Thus, it can be concluded that the better the psychological coping skills possessed by athletes, the lower the level of fear of failure felt. Future research is recommended to use a longitudinal design to test causality and involve a more diverse group of subjects. Furthermore, coaches and trainers are advised to integrate psychological coping skills training, such as goal setting, anxiety management, and self-confidence building, into training programs to reduce fear of failure in athletes